1976
DOI: 10.2307/3897089
|View full text |Cite
|
Sign up to set email alerts
|

Range Burning and Fertilizing Related to Nutritive Value of Bluestem Grass

Abstract: The influence of range burning and nitrogen fertilization on the nutritive value of big and little bluestem in Kansas True Prairie were studied. Late spring burning decreased dry matter, crude fiber, cell wall constituents, cellulose, and lignin, and increased crude protein, ether extract, nitrogen free extract, and ash. Nitrogen fertilization decreased nitrogen free extract and increased crude fiber, lignin, and ash. Big bluestem was higher than little bluestem in nitrogen free extract, and lower in crude fib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

1985
1985
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 9 publications
1
17
0
Order By: Relevance
“…In this study, nitrogen fertilizer had a positive influence on CP content of grass, consistent with the results of Grünow et al (1970), Allen et al (1976), Jones and Wilson (1987), Mitchell et al (1994) and Cohen et al (2004).…”
Section: The Effects Of Nitrogen Supplementationsupporting
confidence: 92%
See 1 more Smart Citation
“…In this study, nitrogen fertilizer had a positive influence on CP content of grass, consistent with the results of Grünow et al (1970), Allen et al (1976), Jones and Wilson (1987), Mitchell et al (1994) and Cohen et al (2004).…”
Section: The Effects Of Nitrogen Supplementationsupporting
confidence: 92%
“…This may be attributed to the new growth of grass with higher CP content in burned grass than in unburned grass (Allen et al, 1976;Christensen, 1977;Tainton et al, 1977;Griffin and Friedel, 1984;McNaughton, 1985;Frost and Robertson, 1987). Fire removed the dead old grass, resulting in young growth of grass tissue.…”
Section: The Effects Of Firementioning
confidence: 99%
“…Lemus et al (2008) noted that the hemicellulose content of switch grass was decreased (<5%) in response to a urea and/or ammonium nitrate fertilization rate increase from 56 to 224 kg N/ha, but no effect of N fertilization was seen on the hemicellulose content of FOS in the present study. Allen et al (1976) also reported no effect on bluestem grass hemicellulose content by urea N fertilization.…”
Section: Influence Of Nitrogen Fertilization On Nutrient Accumulationmentioning
confidence: 96%
“…Furthermore, we think that the plants grow on burned area can provide more nutrition. Some studies showed that herbaceous plants growing on burned area contain more crude protein [22 -25] , less crude fiber [22,23,26] . Thus, the food digestible rate is increased [27] Sciences (KZCX3-SW-343) and "Xi Bu Zhi Guang" Project of CAS and (200233104) and Mr. Wolfgang Frey (former editor of German Journal of Wildlife ) for financing this research.…”
Section: Food Habitat Use Of Tarim Red Deermentioning
confidence: 99%